PDF ANALISIS STRUKTUR DAN KAIDAH KEBAHASAAN TEKS EKSPLANASI PADA PESERTA DIDIK KELAS XI MA MIFTAHUL ULUM ATTOHIRIN GONDANGLEGI MALANG TAHUN 2019/2020 - Yusron Yusuf; Devi (Institute Agama Islam Al-Qolam Malang, 2020)
In the explanatory text it has a plot or structure like other types of text, such as general statements, cause and effect and interpretation. The explanatory text also has linguistic rules which include copula, active verbs, conjunctions, adverbs of time, scientific terms, pronouns. This research is entitled